1996
DOI: 10.1021/jp9532733
|View full text |Cite
|
Sign up to set email alerts
|

Identifiability of Irreversible Intermolecular Two-State Excited-State Processes

Abstract: This report analyzes which kinetic and spectral parameters can be recovered by global compartmental analysis for intermolecular two-state excited-state processes when k 21 [M] (Scheme 1) is negligible. The time-resolved fluorescence of such a photophysical system will decay as a biexponential function with invariant decay times. The ratio of the amplitudes associated with the decay times will depend on [M]. Although the association rate constant k 21 is known to be zero, this knowledge is not helpful in determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…However, its use in photophysics is of recent date. [13][14][15][16][20][21][22][23][24][25] In a photophysical framework a compartment is a subsystem composed of a distinct type of species that acts kinetically in a unique way. The concentration of the constituting species can change when the compartments exchange material through intermolecular (or intramolecular) processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, its use in photophysics is of recent date. [13][14][15][16][20][21][22][23][24][25] In a photophysical framework a compartment is a subsystem composed of a distinct type of species that acts kinetically in a unique way. The concentration of the constituting species can change when the compartments exchange material through intermolecular (or intramolecular) processes.…”
Section: Introductionmentioning
confidence: 99%
“…These two challenges are respectively known in the literature as the distinguishability and identifiability problems 43–54. They raise the fundamental questions of the uniqueness of the specific attributes of a kinetic problem and whether there may be ambiguity in the reaction model even with a good fit between the experimental data and the chosen model.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of numerical identifiability studies can be found in ref. 14,[16][17][18][19][20]51, 70-72.…”
Section: General Conceptsmentioning
confidence: 99%
“…Since the first identifiability study of an intermolecular twostate excited-state process, 12 identification studies of a broad range of models of intermolecular and intramolecular twostate and three-state excited-state processes have been reported [13][14][15][16][17][18][19][20][21][22][23][24] (see ref. 25 and 26 for supplementary literature data).…”
Section: Introductionmentioning
confidence: 99%